Kebijakan Stabilisasi Harga Beras Dalam Kebijakan Pangan Indonesia; Perspektif Liberalis, Marxis dan Public Choice - Taufikurrahman, Muhammad Rifki; Utami, Kristiawati Tri; Koriyah, Koriyah; Darmawan, Dian Rizky Irvan; Nugroho, Setyo (Journal of Society Bridge, 2026)
Abstract: This study examines Indonesia’s rice price stabilization policy through the analytical lenses of liberalism, Marxism, and Public Choice theory. Employing a qualitative methodology grounded in a systematic literature review, the research analyzes secondary data sourced from peer-reviewed journal articles, conference proceedings, government publications, and other scholarly materials published between 2023 and 2025. The analysis adopts a thematic approach to elucidate how each theoretical framework interprets the rationale, mechanisms, and consequences of state intervention in the rice market. The findings indicate that, from a liberal standpoint, policy instruments such as market operations, rice importation, and the establishment of price ceilings constitute distortions to the natural functioning of market forces, thereby weakening competitive incentives and inhibiting innovation. Conversely, the Marxist perspective conceptualizes state intervention as a structural necessity to counteract capitalist domination, mitigate distributive inequality, and secure equitable access to rice as a fundamental public good, particularly for the working class. In contrast, the Public Choice framework highlights that rice stabilization policies are frequently shaped by the self-interested behavior of political elites and bureaucrats, manifested in practices such as political signaling, budget maximization, rent-seeking activities, and information asymmetry. The study concludes that the effectiveness of rice price stabilization is contingent upon the state’s capacity to balance market efficiency, distributive justice, and stringent oversight of opportunistic behavior within the policy process.